PHYSICAL QUALITY OF BALI PORK - Arimbhawa, I Gusti Ngurah Putra; Tenaya, I Wayan Masa; Sukada, I Made (Buletin Veteriner Udayana, 2022)
Pork is one of the important commodities in terms of nutritional, socio-cultural, and economic aspects. The availability of safe, healthy and whole meat is a concrete manifestation for every meat consumer on the market. The purpose of this study was to determine the quality of Balinese pork slaughtered at the traditional slaughterhouse of Penatih Village, Denpasar in terms of subjective tests (color, smell, consistency, and texture). The sample in this study used three-month-old male Balinese pork from three different muscle locations. The collection of organoleptic test data for male Balinese pork was carried out by 10 panelists using the five senses with the method of observation and scoring at three locations of meat on the color, smell, consistency, and texture of the meat. The data obtained were analyzed by the Kruskal-Wallis test and if there was a significant difference, it was continued with the Mann Whitney test. The results showed that organoleptic tests (color, smell, consistency, and texture) of Balinese pork slaughtered at the traditional slaughterhouse of Penatih Village, Denpasar from three different muscle locations (femoral region, vertebral thoracic region, lateral abdominal region) showed no results. significantly different (P>0.05), Based on the results of this study, it can be concluded that the quality of Balinese pork which was tested organoleptically taken at three different muscle locations showed the condition of the organoleptic value in this study was good. different ages as the basic data of the quality of Balinese pork.